Nurturing service-oriented organizational citizenship behavior among tourism employees through leader humility. (March 2021) - Tuan, Luu Trong; Rowley, Chris; Masli, Eryadi; Le, Viet; Phuong Nhi, Luong Thi
Abstract: Though the effectiveness of leader humility has been established, does leader humility activate followers to serve customers in the tourism sector beyond their assigned roles? Our study aims to address this question by drawing upon the conservation of resources theory to propose that leader humility promotes service-oriented organizational citizenship behavior (service-oriented OCB) among tourism employees through the mediating role of their job crafting. Our study further assumes the moderating role of socially responsible human resource practices (SRHR practices) for the relationship between leader humility and employee job crafting. Utilizing a two-wave research design, the study garnered the data from 894 employees and 136 managers working in tour companies based in Vietnam. The analysis of the data via the multilevel structural equation modelling lent credence to the proposed research model. Our study not only advances the leadership humility literature in the tourism discipline but also provides a guideline for practitioners on how to optimally adopt leader humility in promoting service-oriented OCB among tourism employees.